A Thermal‐Pressed Strategy for Crystal Growth and Boundaries Self‐Fusion of Mixed‐Halide Perovskite Films against Halide Phase Segregation. Issue 19 (6th June 2022) - Zhang, Teng; Zhang, Li; Zhu, Guanglu; Cui, Deliang; Wang, Qilong; Lian, Gang; Zheng, Zhaoke; Yu, Haohai
Abstract: All‐inorganic mixed‐halide perovskite CsPbI3− x Br x materials have attracted extensive attention in optoelectronics due to upgraded stability and tuned bandgap. Unfortunately, undesired halide phase segregation by ion migration under illumination deteriorates photoelectrical performance and long‐term stability of devices. The severity of phase segregation is prone to occur at grain boundaries and relies on surface/interface defects. Herein, a thermal‐pressed (TP) crystal‐growth strategy is proposed to realize sufficient grain growth and boundary fusion simultaneously in a series of CsPbI3− x Br x films. The large‐sized crystals (20–40 µm), self‐fused boundaries, and single‐crystal‐like surface effectively block photoinduced ion migration. The TP‐based CsPbI3− x Br x films maintain excellent long‐life photostability over one year and exhibit markedly suppressed halide phase segregation under continuous laser illumination. Consequently, the TP‐based photodetector devices exhibit superior long‐term stability under laser illumination with different wavelengths. Abstract : Based on a universal thermal‐pressed strategy, ion migration "freeways" for photoinduced halide phase segregation is effectively eliminated via sufficient crystal growth and boundaries self‐fusion of CsPbI3− x Br x ( x  = 1–2) perovskite films. Accordingly, the high‐quality CsPbI3− x Br x ‐based film device exhibits superior photostability.